2018
DOI: 10.1002/kin.21209
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of elementary reactions and kinetics of radical‐initiated methyl methacrylate polymerization in the presence of ferrocene

Abstract: On the basis of quantum chemical modeling, a kinetic scheme of methyl methacrylate polymerization initiated by benzoyl peroxide in the presence of ferrocene was proposed. The process runs by mechanism, which includes the reactions of free radical polymerization, and the reactions leading to formation and operability of two type coordination active sites that are capable of converting into each other. On the basis of the proposed scheme, a kinetic model was developed. This model quantitatively described the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…It has been experimentally established that the increase of the ferrocene concentration in the radical coordination polymerization of methyl methacrylate contributes to the smoothing of the gel effect. 41 The time dependencies of the methyl methacrylate conversion polymerized on the coordination active sites for this process have a linear form, 41 5, 7, and S5−S8, all (e)] basically corresponds to the form of similar conversion dependencies of the poly(methyl methacrylate) molecular weights obtained as a result of classical radical polymerization.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…It has been experimentally established that the increase of the ferrocene concentration in the radical coordination polymerization of methyl methacrylate contributes to the smoothing of the gel effect. 41 The time dependencies of the methyl methacrylate conversion polymerized on the coordination active sites for this process have a linear form, 41 5, 7, and S5−S8, all (e)] basically corresponds to the form of similar conversion dependencies of the poly(methyl methacrylate) molecular weights obtained as a result of classical radical polymerization.…”
Section: Resultsmentioning
confidence: 88%
“…It is typical that it would not be observed during the radical coordination polymerization of methyl methacrylate in the presence of initiating system "benzoyl peroxide + ferrocene", when the slope of the time dependence of conversions U ci would not increase during the process. 41 Thus, it can be concluded that the radical coordination polymerization of methyl methacrylate in the presence of ferrocene and in the presence of zirconocene dichloride has a qualitative difference. In the first case, polymerization is characterized by the parallel functioning of radical and coordination channels for the formation of poly(methyl methacrylate) chains.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations